Politik Hukum Batas Usia Anak dalam Peraturan Perundang-Undangan di Indonesia - Setiawan, Setiawan; Fatmawati O, Nynda (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to examine and analyze the implications of inconsistent child age limits across various legislations in Indonesia on legal certainty and child protection. The research methodology includes identifying and comparing child age limits in legislation, as well as analyzing the impact of this inconsistency on legal certainty and the implementation of child protection. The findings indicate that divergent age limits in legislation result in uneven legal protection and create legal uncertainty. Moreover, this inconsistency affects daily legal practices by law enforcement officials, including judges and lawyers. The study recommends harmonizing child age limits across legislations to enhance legal certainty and the effectiveness of child protection in Indonesia. Consequently, it is hoped that every child can grow and develop in a safe and supportive environment.